Design of car hood of sandwich structures for pedestrian safety. (1st January 2013) - Teng, Tso-Liang; Liang, Cho-Chung; Shih, Chien-Jong; Nguyen, Manh-Trung
Vehicle safety factors should simultaneously consider occupant and pedestrian safety, given that pedestrians are the third largest category of traffic fatalities. Most pedestrian deaths occur due to traumatic brain injury, resulting from the hard impact of the human head against the vehicle's stiff hood or windshield. Therefore, how to design a pedestrian-friendly vehicle and propose a new hood structure is a matter of urgency for minimising pedestrian head injuries. In this study, three kinds of sandwich hood structures are proposed for reducing pedestrian head injuries, including carbon fibre-reinforced polycarbonate, carbon fibre-reinforced foam and aluminium-reinforced polycarbonate. In assessing the friendliness of vehicle hoods, this study adopts the EEVC/WG17 regulations on headforms for hood tests. The finite element method is used to simulate the impact between the vehicle's hood and the headform impactor. The software used in simulation is LS-DYNA. The results predicted by the headform–hood tests show that the hood structure with aluminium-reinforced polycarbonate material provides enough absorption capability to protect pedestrians from the impacts of accidents. It is also stiff enough to keep pedestrians' heads away from the inner parts of the engine cavity. The analysis models and sandwich materials proposed herein contribute to efforts to design vehicle hood structures and pave the way for developing pedestrian protection technologies.